White Layer Thickness Variation in Die Sinking EDM - Oßwald, Kai; Schneider, Sebastian; Klink, Andreas; Bergs, Thomas (Procedia CIRP, 2022)
Surfaces that were machined by Electrical Discharge Machining (EDM) inevitably exhibit a thin layer of resolidified material, commonly called “white layer”. It is usually regarded as disadvantage of ED machining as it induces tensile residual stresses to the parent material and therefore facilitates the formation of cracks. It therefore was subject to a number of scientific investigations that often dealt with its (non-)crystalline structure or the stress induction. Some research groups have also focused on the thickness of the white layer. However, the variation of its thickness has not yet been investigated comprehensively and therefore constitutes the focus of this work. Experiments were conducted on a conventional sinking EDM machine. A heat-treatable steel was used as a workpiece material and graphite was used for the tool electrode. The influence of the discharge duration te as well as the discharge current ie on the white layer formation were investigated. Results show that significant thickness variations occur on every ED machined surface and that increasing discharge energy leads to an increase of both, white layer thickness as well as its variation.